Eminent outlaws the gay writers who changed America - Bram, Christopher (Twelve, 2012)
Describes how the trailblazing, post-war gay literary figures, including Tennessee Williams, Gore Vidal, Truman Capote, and Allen Ginsberg, paved the way for newer generations, including Armistead Maupin, Edmund White, and Edward Albee.